Exploring Common Pronunciation Errors Faced by English Majors at a Vietnamese Public University - Luu, Phi Dat; Nguyen, Phat Tan (Universitas Muhammadiyah Yogyakarta, 2026)
Background: Although pronunciation is fundamental to communicative competence, it remains a major challenge for English as a Foreign Language (EFL) learners. This study fills a scholarly gap by presenting beyond descriptive analysis, providing empirical evidence to improve educational strategies and promote awareness of mistakes in high-stakes academic settings. Objective: This study investigates the prevalence and nature of pronunciation errors among EFL students at a Vietnamese public university, while examining the influence of gender and proficiency levels on these errors. Methods: Utilizing a cross-sectional quantitative design, the study sampled 186 first-year English majors. Data were collected using the Common English Pronunciation Errors Questionnaire (CEPEQ) and were validated through an independent diagnostic performance assessment. Statistical analyses, including independent-samples t-tests and one-way ANOVA, were used to compare group differences. Findings: Results indicated a moderate error level, with segmental features (individual vowels and consonants) posing greater difficulty than suprasegmental ones (stress, rhythm, and intonation). Significant differences were found by gender and proficiency level in segmental and overall pronunciation errors, with higher-proficiency learners reporting greater error awareness; however, no significant differences emerged in suprasegmental aspects. Conclusion: The findings highlight that segmental features remain the primary hurdle for Vietnamese EFL learners. The study suggests that pedagogical interventions should integrate automated speech evaluation and speech-recognition technology to prioritize articulatory accuracy alongside prosodic awareness, particularly for lower-proficiency students.